Jaringan Komunikasi Pemasaran Kakao di Kecamatan Anreapi, Kabupaten Polewali Mandar, Provinsi Sulawesi Barat - Agus Raharjo; Pudji Muljono; Krishnarini Matindas (Institut Pertanian Bogor, 2017)
Effective and efficient marketing is a key in increasing farmers income. Interaction between farmers would involve the sharing of information about marketing and creating a communication network among cocoa farmers. Communication networks should be developed in cocoa marketing because it can provide information to farmers about the price and quality that consumers needs and more profitable marketing purposes. The measure of this study used analysis of communication networks which is ‘centrality’. Centrality refers to the position of actors (nodes) in the overall network and see how centrals actors in the network. Centrality measurements used in this study are degree centrality, closeness centrality, and betweeness centrality. The purposes of this study were 1) to describe the individual characteristics of farmers, media exposure by farmers, and communication network 2) to analyze the correlation between farmers characteristic and communication network analysis and 3) to analyze the correlation between media exposure and communication network analysis. The result of this study showed that 1) the variable of farmer characteristics such as age was relatively adult, formal education was relatively low, the area of land cultivated was relatively moderate, farming experience was relatively high, and group experiences is relatively high on Tunas Harapan group and moderate on Bunga Harapan group. The variable of media exposure such as media ownership, frequency, and duration of media use was relatively low. The central actor on Tunas Harapan group was the group leader while the central actor on Bunga Harapan group was the group member. 2)Farmer characteristic correlated with degree centrality was formal education and farmer characteristics correlated with closeness centrality were the area of land cultivated and experience of the group. 3) Media exposures correlated with degree centrality were media ownership, the frequency of media use and the duration of media use then media exposure of farmer correlated with betweeness centrality were the frequency of media use and duration of media use.